Nominations of the plant world lingocultural aspect - Aizhan Shormakova3, Arailym Shormakova1, Lira Ibraymova2,; Laura Daurenbekova5, Botakoz Nurzhanova4, (Opción, 2019)
The article investigates the peculiarities of research in thelinguistic and cultural aspect of the flora of the Kazakh language andthe conceptual sphere of vegetation, the cognitive level of the plant«Zhusan» in the Kazakh language via comparative qualitative researchmethods. As a result, the wormwood is a phytonem that have reachedthe conceptual level. In conclusion, each language is a symbolicsystem that preserves national culture, its culture, its cognitive andtaste, its character and its consciousness, its trades and traditions, itstraditions and wisdom. Therefore, it is most important to study it incognitive linguistics.